Exploring Cell Wall Composition and Modifications During the Development of the Gynoecium Medial Domain in Arabidopsis - Herrera-Ubaldo, Humberto; de Folter, Stefan (Frontiers in Plant Science, 2018)
In Arabidopsis, the gynoecium, the inner whorl of the flower, is the female reproductive part. Many tissues important for fertilization such as the stigma, style, transmitting tract, placenta, ovules, and septum, comprising the medial domain, arise from the carpel margin meristem. During gynoecium development, septum fusion occurs and tissues form continuously to prepare for a successful pollination and fertilization. During gynoecium development, cell wall modifications take place and one of the most important is the formation of the transmitting tract, having a great impact on reproductive competence because it facilitates pollen tube growth and movement through the ovary. In this study, using a combination of classical staining methods, fluorescent dyes and indirect immunolocalization we analyzed cell wall composition and modifications accompanying medial domain formation during gynoecium development. We detected coordinated changes in polysaccharide distribution through time, cell wall modifications preceding the formation of the transmitting tract, mucosubstances increase during transmitting tract formation, and a decrease of mannan distribution. Furthermore, we also detected changes in lipid distribution during septum fusion. Proper cell wall composition and modifications are important for postgenital fusion of the carpel (septum fusion) and transmitting tract formation, because these tissues affect plant reproductive competence.